Effective protection of environmental law - Torres López, Edgardo (2008)
The progressive damage of the environment caused by human beings, have created the environmental law, constituted by norms that aims to the correct use of the environment, avoiding the pollution, destruction and the lack of balance; assuring the harmony between the individual and public interest and the protection of the eco system. Environment law aims to protect the ecology, the jungle, the forest and the balanced development of the human life in a healthy habitat; likewise, avoid the progressive destruction of nature and life. Within the framework of this discipline, the environment law provides the legal mechanisms for the protection of the environment. The government, according to the current legislation, is in charge of the direction and supervision of the correct use of the environment. To fulfill the objectives it must formulate a strategy to regulate the environment.